Administration Timing and Efficacy of Tocilizumab in Patients With COVID-19 and Elevated IL-6 - Li, Pan; Lu, Zhengmao; Li, Qiang; Wang, Zhenmeng; Guo, Yan; Cai, Chen; Wang, Shengyun; Liu, Peng; Su, Xiaoping; Huang, Yi; Dong, Yuchao; Qiu, Wenjuan; et al. (Frontiers in Molecular Biosciences, 2021)
Background: Tocilizumab (TCZ), an interleukin-6 receptor antibody, has previously been used for treating the coronavirus disease 2019 (COVID-19) patients, but lacking of data regarding the administration timing of TCZ. Objectives: This study aims to evaluate the timing and efficacy of TCZ in the treatment of patients with COVID-19. Methods: Laboratory-confirmed COVID-19 patients with an elevated IL-6 level (>10 pg/mL) were offered TCZ intravenously under compassionate use. Clinical characteristics, laboratory tests and chest imaging before and after administration of TCZ were retrospectively analyzed. Results: A total of 58 consecutive patients who met the inclusion criteria and with no exclusion criteria were included. Of these, 39 patients received TCZ treatment and 19 who declined TCZ treatment were used as a control cohort. In the TCZ-treatment group, 6 patients (15.4%) were in mild condition, 16 (41.0%) were in severe condition and 17 (43.6%) in critical condition. After TCZ treatment, 27 patients (69.2%) were improved and 12 (30.8%) died. Compared with the improvement group, patients in the death group had higher baseline levels of IL-6 (P = 0.0191), PCT (P = 0.0003), and lower lymphocyte percentage (P = 0.0059). Patients receiving TCZ treatment had better prognosis than those without TCZ treatment (P = 0.0273). Furthermore, patients with baseline IL-6 level ≥100 pg/mL in the TCZ-treatment group had poorer clinical outcomes than those with IL-6 level <100 pg/mL (P = 0.0051). Conclusions: Administration of TCZ in an early stage of cytokine storm (IL-6 level <100 pg/mL) may effectively improve the clinical prognosis of COVID-19 patients by locking IL-6 signal pathway.